ఉన్నతస్థాయి తెలుగు పాఠ్యపుస్తకం - (:unkn) unknown (My University, 2019)
It aims at providing the learners with the crucial aspects of Telugu Language and its culture, Land, Literature, Customs and habits of the Telugus and other socio-cultural aspects.
Telugu Advanced Course Text Book
Keywords: Telugu